Supplemental instruction leader development and student learning in a historically Black college context: A mixed-methods study of virtual peer-led learning - Brown, Lisa (American Journal of STEM Education, 2026)
This mixed-methods study examines Supplemental Instruction (SI) Leader experiences at a Historically Black College or University during the transition to virtual learning. Using a convergent design, data from undergraduate SI Leaders (N = 10) were collected via the SILVP Inventory. Quantitative results indicated strong perceived student learning, moderate leader development, and more variable program logistics. Qualitative findings highlighted interconnected themes of student engagement, leadership growth, and challenges in virtual delivery. Integrated results suggest that SI operates as a reciprocal system in which facilitating peer learning supports leader development. This study advances a conceptual double-impact model, positioning SI as a socially mediated learning environment that co-produces student outcomes and leadership development within culturally affirming institutional contexts.